Get Smart. Season 1 [videorecording (DVD)] - Brooks, Mel, 1926-; Henry, Buck (HBO Home Entertainment, 2015)
Bumbling spy Maxwell Smart, Agent 86 for CONTROL, battles the forces of nemesis agency KAOS with a great deal of help from his partner Agent 99.